Perbandingan Biaya dan Waktu Antara Diversion Channel Dengan Pemancangan Steel Sheet Pile Pada Pekerjaan Pemasangan Double U-Ditch Precast - Mukhamad Afif Salim; Agus B Siswanto; Agung Gagas E (Jurnal Teknik Sipil Unaya, 2021)
Methods used in the implementation of the project on precast U-ditch installation work, one of which is by steel sheet pile erection method and Diversion Channel method. The analysis data required for the comparison of these two methods is secondary data obtained from the implementing party in the form of RAB, time schedule, implementation picture. In this analysis, alternative methods are planned by comparing in terms of cost and execution time. By analyzing the comparison of steel sheet pile erection method with Diversion Channel method, obtained results on the erection method with Steel sheet pile has a work cost of Rp.7,766,567,860 with an implementation time of 117 days, while with the Diversion Channel method the required cost is Rp.3,894,630,735 with an implementation time of 100 days so that there is a cost efficiency of 49.85% and a faster time of 17 days with diversion channel method.